STRATEGI KEBERLANJUTAN PROGRAM URBAN FARMING DI KELURAHAN PENGADEGAN JAKARTA SELATAN - Fretzelita Gatra Annisa; tedi tedi tedi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
The background of this research is the result of the overcrowding that occurred in the capital city of DKI Jakarta which has caused land narrowing and a lack of awareness in protecting the environment in the people of Jakarta. A dirty environment causes a negative impact on public health, both from unhealthy air circulation, food quality that is not guaranteed for cleanliness. The Pengadegan area is one of the areas in Jakarta that has narrow land and people who lack awareness of protecting the environment. Urban farming is an effort to increase public knowledge in protecting the environment. Community empowerment through urban farming is usually carried out in urban areas, by optimizing areas as urban environmental management. The purpose of this study was to determine the sustainability strategy for the urban farming program in the Pengadegan area focused on Alley C. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques used by conducting interviews, observation, documentation and literature studies. The results of the research show that there are 3 components of sustainability, namely: 1) Ecological sustainability, that is, looking at the state of the environment and awareness of the community in protecting the environment. 2) Economic sustainability, namely, seen from the results of the harvest can be useful in life. 3) Socio-cultural sustainability, namely, strategies that maintain aesthetic values and social interaction in society.